Front Cover: A Series of 2‐((1‐Phenyl‐1H‐imidazol‐5‐yl)methyl)‐1H‐indoles as Indoleamine 2, 3‐Dioxygenase 1 (IDO1) Inhibitors (ChemMedChem 14/2021). (18th July 2021) - Zheng, Yong; Stafford, Paul M.; Stover, Kurt R.; Mohan, Darapaneni Chandra; Gupta, Mayuri; Keske, Eric C.; Schiavini, Paolo; Villar, Laura; Wu, Fan; Kreft, Alexander; Thomas, Kiersten; Raaphorst, Elana; et al.
Abstract : The Front Cover illustrates the 'molecule to mind' structural hierarchy of pathology and symptoms arising from Alzheimer's disease. Although Alzheimer's presents as a disorder of thought, memory, and cognition, it is a disease that we seek to treat not at the cellular level, but at the molecular level. Given that the brain is the most complex structure in the universe, and that Alzheimer's is the most complex disease of brain, the search for new treatments must address all possible avenues. The brain's immune system is an important emerging druggable target; we describe our identification of indoleamine 2, 3‐dixoygenase inhibitors as putative disease modifying therapies for Alzheimer's. More information can be found in the Communication by Donald F. Weaver et al.